2002
DOI: 10.1097/00006676-200211000-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Detection of Pancreatic Carcinoma by Combined Plasma K -ras Mutations and Serum CA19-9 Analysis

Abstract: The results indicate that plasma K mutation analysis combined with serum CA19-9 determination could detect the majority of cases of pancreatic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 20 publications
1
17
1
1
Order By: Relevance
“…Thus, occurrence of mutations in samples analysed in our study can hardly be compared with incidences found by other investigators (Mulcahy et al, 1998;Castells et al, 1999;Dianxu et al, 2002;Maire et al, 2002). The percentages of plasma samples with mutated Ki-ras gene found to date in the existing studies differ in a wide range of 27 -81%, which might reflect collection of samples at different tumour stages and various sensitivities of the assays for detection of Ki-ras point mutations.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Thus, occurrence of mutations in samples analysed in our study can hardly be compared with incidences found by other investigators (Mulcahy et al, 1998;Castells et al, 1999;Dianxu et al, 2002;Maire et al, 2002). The percentages of plasma samples with mutated Ki-ras gene found to date in the existing studies differ in a wide range of 27 -81%, which might reflect collection of samples at different tumour stages and various sensitivities of the assays for detection of Ki-ras point mutations.…”
contrasting
confidence: 56%
“…The percentages of plasma samples with mutated Ki-ras gene found to date in the existing studies differ in a wide range of 27 -81%, which might reflect collection of samples at different tumour stages and various sensitivities of the assays for detection of Ki-ras point mutations. Dianxu et al (2002) tested 37 of 41 patients (90.2%) with pancreatic cancer positive when plasma Ki-ras mutation analysis was combined with elevated CA 19-9 serum levels (437 Units ml À1 ). In our study, we detected Ki-ras mutant alleles only in four out of 10 patients with high CA 19-9 levels.…”
mentioning
confidence: 99%
“…Mulcahy et al have found a K-ras mutation in plasma DNA in patients who were diagnosed with pancreatic cancer 5 to 14 months later and did not find these alterations in patients with chronic pancreatitis or healthy subjects [83]. The detection of K-ras mutation in plasma DNA and an increase in the CA 19-9 tumor marker are independent events in pancreatic cancer and test sensitivity reached 90% when both tests were combined [84]. A longitudinal prospective study by Gormally et al has shown that detection of KRAS2 and p53 mutations in plasma of healthy individuals is associated with an increased risk of bladder cancer [85].…”
Section: Cirdna Mutations In Different Cancersmentioning
confidence: 99%
“…However, plasma KRAS mutation was also detected in two patients with chronic pancreatitis. Dianxu et al (2002) tried to establish the diagnostic value of codon 12 KRAS mutations in plasma combined with serum CA19-9 in 58 consecutive patients with a suspected pancreatic mass. Forty-one patients were subsequently diagnosed with pancreatic adenocarcinoma.…”
Section: Pancreatic Cancermentioning
confidence: 99%